Penerapan Teknologi Augmented Reality sebagai Model Media Edukasi Kesehatan Gigi Bagi Anak Sekolah Dasar - Rumaisha Soumena; Dwi Rezky Aulyah; Pariati Pariati; Faradillah Usman (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
The use of augmented reality (AR) technology in educational media is expected to attract children's attention and make lessons more interesting to follow. This is because it can convey dental health content interactively and virtually in three dimensions in real time. To evaluate the effectiveness of the application of Augmented Reality (AR) technology as an educational media model in increasing the knowledge and understanding of elementary school children about dental and oral health, as well as to assess the potential of this technology as an interactive and interesting learning method for children. This research was carried out in November 2023. The population in this study is the total number of students of SD Minasa Upa. The sample was 60 people. The type of research used is a quasi-experimental design with a One Group Pretest-Poster research design. The design of this study aims to find out whether there is an influence on the use of AR technology as a dental health education medium in children. Increasing the knowledge of respondents. The results showed that 13 respondents (92.86%) experienced an increase in knowledge from bad to good, 1 respondent (7.14%) experienced an increase in bad knowledge to adequate, 14 respondents (87.5%) experienced an increase in knowledge less to good, and 2 respondents (12.5%) experienced an increase in knowledge less to adequate. Concept design activities include the selection of themes, namely the system can be used as an object of presentation or delivery of material to children so that the objects made need to pay attention to the selection of colors, shapes, sizes, arrangement of images and interesting materials.